Pro-Choice March Through Downtown San Francisco to City Hall - Watkins, Howard::::::::: (1989)
Howard Watkins wearing Giants cap and yellow "DAD" shirt with Dorothy Ehrlich marching in front of American Civil Liberties Union banner